2022
DOI: 10.1186/s12889-022-13478-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a menstrual hygiene intervention in urban and rural schools in Bangladesh: a pilot study

Abstract: Girls’ menstrual experiences impact their social and educational participation, physical and psychological health. We conducted a pilot study to assess the acceptability and feasibility of a multi-component intervention intended to support menstruating girls; improve menstrual care knowledge, practices, and comfort; and increase school attendance.We conducted a pre/post evaluation of a 6-month pilot intervention in four schools (2 urban, 2 rural) in Dhaka, Bangladesh. We selected 527 schoolgirls (grades 5 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…Intervention components included provision of schoolteacher-led puberty and menstruation education, improved waste disposal facilities, and distribution of menstrual materials and menstrual cycle tracking calendars (among other activities). Details about the study context, school selection and characteristics, and the main study’s intervention activities and evaluation methods have been presented separately [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intervention components included provision of schoolteacher-led puberty and menstruation education, improved waste disposal facilities, and distribution of menstrual materials and menstrual cycle tracking calendars (among other activities). Details about the study context, school selection and characteristics, and the main study’s intervention activities and evaluation methods have been presented separately [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Menstrual hygiene management (MHM) in schools is subpar due to limited access to menstrual hygiene knowledge and facilities [ 1 , 2 ]. Adolescents must manage their menstruation at home and at school, as it is a vital part of their lives [ 3–5 ]. Worldwide studies conducted over the last ten years have demonstrated the difficulties schoolgirls encounter in managing their menstruation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents are frequently misled and unprepared for menstruation due to a lack of knowledge and MHM facilities and practices and social stigma [ 11 , 12 ]. Since they spend six hours in school, it’s critical that they have access to gender-specific sanitation facilities that are both clean and functional [ 3 ]. Poor menstrual hygiene habits are frequently caused by inadequate water, sanitation, and hygiene (WASH) facilities, a lack of privacy, and a lack of gender-specific wash facilities at schools [ 3 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention was piloted and evaluated from August 2017 to April 2018 in four urban and rural schools in Bangladesh. The effects of the intervention on primary outcomes are presented separately [ 27 ]. This paper is a sub-study that aimed to explore the breadth of information regarding menstruation that Bangladeshi adolescents sought from their schoolteachers during the intervention pilot, demonstrating the types of knowledge they desired yet had been unable to reliably access.…”
Section: Introductionmentioning
confidence: 99%